DDIS-07. MSC-DERIVED EXOSOMES AND microRNA IN GLIOMA THERAPY. (5th November 2018) - Hasan, Irtiza; Momin, Eric; Gumin, Joy; Adachi, Satoshi; Kerrigan, Brittany; Hossain, Anwar; Lang, Frederick
Abstract: Glioblastoma (GBM), the most common and deadly adult brain tumor, is notoriously resistant to therapy, not only because of the presence of Glioma Stem-like Cells (GSCs) but also because of the formidable delivery challenges imposed by the blood-brain barrier. Consequently, there is an urgent need to identify effective therapeutics and to elucidate successful strategies for delivering these new agents to GBMs. A promising new therapeutic approach is treatment with microRNAs (miRs), which are small, noncoding RNA that are powerful regulators of gene expression. We have shown that restoration of tumor suppressor miRs that are down-regulated in GBMs is capable of inhibiting the growth of GSCs. Despite the therapeutic potential of miRs, however, it is currently unknown which miRs will be most effective against GBMs and how these miRs will be delivered. To define miRs that are most effective against GBMs, we undertook a "candidate approach" based on a literature review and tested miR-124 & miR-128 as potential anti-glioma miRs. These initial analyses made it clear that a comprehensive evaluation of miRs that inhibit GBMs was lacking. Therefore, we have undertaken an unbiased high throughput screen of 578 miRs against a panel of patient-derived GSCs representing all TCGA-GBM classes. We identified 50 miRs that are highly effective at inhibiting GSCs regardless of TCGA subtype. Further, we demonstrated that exosomes derived from ex-vivo cultured mesenchymal stem cells (MSCs) can systemically deliver anti-glioma miRs to GBMs. Exosomes are naturally occurring nanovesicles that function as intercellular transport vehicles. MicroRNA-loaded exosomes (Exo-miRs) can be isolated and then used to deliver the miR to GBMs. Most importantly, we have shown that when systemically administered into mice, Exo-miRs "home" to brain tumors resulting in down-regulation of the miR target genes. These results suggest that MSC-derived exosomes can be used as systemic delivery vehicles of anti-glioma miRs.